A Study of Hypothesis Testing On the Black-Scholes Option Pricing Model - Chin, Jian Quan; Mahathir Bin Mohamad (Enhanced Knowledge in Sciences and Technology, 2022)
The analysis of the financial market has been one of the primary concerns of the academics for the last few decades. Trading activity in stock market has risen dramatically in recent years which contributing to high volatility in the option values. With the ongoing growth of the financial market in today’ globe, there has been a continual creation of numerous financial instruments. Derivative investment is an essential component of the stock market. There are several forms of derivatives that may be utilized for risk management, speculation, and position hedging. In this research is to investigate the derivative option contract. Option contract is an agreement between two parties to purchase or sell an asset at a defined future date and price. In this research, we are going to study the uses of Black-Scholes model of option’s prices formula, compute the theoretical prices of options of the stocks by using Black-Scholes Option Pricing models and the significant difference between Black-Scholes Option Pricing models prices and the actual option’s prices. Derivatives are financial instruments whose value is determined by the performance of an underlying assets. The world of financial derivatives can differ greatly from one another. The option derivative trading is the most important components in this research. In this research will used Black-Scholes Model to find the fair price of the underlying assets. The data are collected from KLSE screener. The data process by the SPSS software to compute the paired sample t test. It was found that there was significant difference between the Black Scholes Option Pricing Models and the actual option’s price at 95% significant level.